Application of toughness limit in assessment of soil compaction identifiers - Satoru Shimobe; Eyyüb Karakan; Alper Sezer (Građevinar)
In geotechnical engineering, the precise evaluation of compaction parameters is essential for quality control assessment. One option is the use of the toughness limit (TL), concisely defined as the water content, at which the behaviour of fine-grained soils evolves from an almost adhesive-plastic to tough-plastic. A database consisting of more than 1000 test results, including the compaction characteristics and Atterberg limits, was compiled to establish correlations between the TL, Atterberg limits, optimum degree of saturation, and compaction properties. The results revealed that the TL has the potential to evaluate many indices and compaction identifiers for different types of soils.